African traditional abdominal massage in pregnancy resulting in antepartum uterine rupture, abruptio placenta and foetal demise – a case report - Amadi, Simeon C.; Awoyesuku, Peter A.; Iwo-Amah, Rose S.; Ibeabuchi, Sandra U. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
The practice of abdominal massage dates to years ago and associated with foetal and maternal morbidity and mortality when undertaken by untrained traditional birth attendants in our setting. We present a 30-year old G3P2+0 with uterine rupture and intra-uterine foetal death following abdominal massage. She was resuscitated and had emergency exploratory laparotomy and repair of uterine rupture.